Gastro-protective effects of the phenolic acids of Macrotyloma uniflorum (horse gram) on experimental gastric ulcer models in rats. (1st December 2015) - Panda, Vandana; Suresh, Swetha
Abstract: Macrotyloma uniflorum Lam. (Verdc.) known as horse gram is an underutilized and unexplored food legume distributed throughout Asia and Africa. Its seeds are rich in phenolic acids, p- coumaric acid being the most abundant phenolic acid. The present study evaluates the antiulcer and antioxidant activity of the hydroalcoholic extract of the seeds of M. uniflorum (MUSE) and p- coumaric acid against indomethacin (non-steroidal anti-inflammatory drug) and absolute ethanol (necrotizing agent) induced ulcers in rats. Pre-treatment with MUSE and p- coumaric acid showed a dose-dependent decrease in the ulcer index in both models. MUSE and p- coumaric acid elicited significant antioxidant activity by attenuating the ulcer elevated levels of malondialdehyde and restored the ulcer-depleted levels of reduced glutathione and the antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase. In conclusion, MUSE possesses potent antiulcer activity which may be attributed to an underlying antioxidant activity.